PERANCANGAN DAN IMPLEMENTASI SISTEM REPLIKASI DATABASE TERDISTRIBUSI PADA FAKULTAS TEKNIK UNIVERSITAS HALU OLEO - Muhammad Hidayat Darmawan; Isnawaty Isnawaty; Subardin Subardin (Informatics Engineering Department of Halu Oleo University, 2018)
Current technological developments are very influential on the process of data distribution that is demanded fast because every second of information can change. One of the methods used in data exchange is to use data replication in a distributed database. The speed of the process and the number of rows that can be replicated in units of time are some of the things that can be taken into consideration when trying to determine how to replicate data in a distributed database.In replication, a software is used to find or more precisely track changes that occur in a database. After changes in one database are identified and known, then changes are made so that all databases are the same as other databases.This study implements two computers consisting of master and slave, each of which is a database server that is connected to each other in the network. The test results obtained in this study are that with the database replication, every data that is stored periodically always backups the slave computer.Keywords—Replication, Database, Distributed Database DOI : 10.5281/zenodo.1493829